A Proposed Conceptual Model of Teacher Turnover Intention in the Vocational High Schools in Indonesia - Jajat Sudrajat; Siow Heng Loke; Syafwandi; Efri Syamsul Bahri; Ibar Adi Permana (Pusat Riset dan Inovasi Nasional, 2022)
The description of the determinants of teacher turnover intention in Vocational High School (SMK) is still not optimally depicted in Indonesia. This condition is due to the limited number of special studies that focus on teacher turnover intentions for vocational school teachers. At the same time, the role of vocational school teachers is essential for the sustainability of educational institutions. Therefore, this study aims to build a conceptual model that determines teacher turnover intention. Literature research data was collected between 2006 and 2021, sourced from Google Scholar. In addition, the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and bibliometric approaches were used for data analysis. The findings of the study lead to the development of a conceptual model to determine teacher turnover intention, which includes five variables: job satisfaction, interpersonal stress, efficacy, prosocial motivation, and organizational culture. It was found that teacher turnover intention can be measured through three dimensions: the possibility of individuals leaving the organization, teachers' cognitions and attitudes, and the frequency and intensity of intentions.